2017
DOI: 10.1159/000477120
|View full text |Cite
|
Sign up to set email alerts
|

Let-7a Inhibits T-Cell Proliferation and IFN-γ Secretion by Down-Regulating STAT3 Expression in Patients with Psoriasis

Abstract: Objective: This study aimed to explore the effects of STAT3 targeting by let-7a on T-cell proliferation and IFN-γ secretion in psoriasis. Methods: From January 2013 to January 2015, 40 patients with psoriasis (psoriasis group) and 38 volunteers undergoing plastic surgery (control group) were enrolled in this study. Pearson correlation analysis was performed to evaluate the correlation between let-7a and STAT3 expression. T-cells were isolated and subjected to different transfection methods. A dual luciferase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…As previously reported, miRNAs have the ability to post‐transcriptionally mediate the expression of numerous genes . Moreover, it has demonstrated that STAT3 is one of the target genes of let‐7a . A prior study concluded that let‐7a targets and negatively regulates STAT3 in HCC cells .…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…As previously reported, miRNAs have the ability to post‐transcriptionally mediate the expression of numerous genes . Moreover, it has demonstrated that STAT3 is one of the target genes of let‐7a . A prior study concluded that let‐7a targets and negatively regulates STAT3 in HCC cells .…”
Section: Discussionmentioning
confidence: 80%
“…32 Moreover, it has demonstrated that STAT3 is one of the target genes of let-7a. 15 A prior study concluded that let-7a targets and negatively regulates STAT3 in HCC cells. 33 The targeting relationship between let-7c and STAT3 in alveolar macrophages has been speculated in previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, lack of good knowledge of etiopathogenesis impairs the development of an effective treatment. However, recent studies of molecular mechanisms in psoriatic patients give a new promise for effective therapy [25][26][27].…”
Section: Introductionmentioning
confidence: 99%